Retrograde Hysterectomy Approaches in Difficult Gynaecology Surgery - I Gde Sastra Winata; Ongko, Eric Gradiyanto; I Nyoman Gede Budiana; I Nyoman Bayu Mahendra; Kade Yudi Saspriyana; Pande Kadek Aditya Prayudi; Arlando Martino Anapaku; Florencia (Indonesian Journal of Perinatology, 2025)
Hysterectomy remains one of the most frequently performed gynecological surgeries worldwide. While extra-fascial hysterectomy is the standard abdominal approach, complex cases involving large fibroids, severe endometriosis, adhesions, or malignancy often require alternative techniques such as the Aldridge method or retrograde hysterectomy. These challenging situations are associated with distorted pelvic anatomy, fibrosis, and adhesions, increasing the risk of complications, including injury to adjacent organs. This article reviews strategies and operative steps in managing complex abdominal hysterectomies, with emphasis on retrograde hysterectomy as a valuable approach when the cervicovaginal junction cannot be clearly identified or when extensive adhesions are present. The surgical technique is described step by step, supported by imaging and intraoperative findings, and highlights methods such as hydrodissection and careful dissection around critical structures to minimize morbidity. Preoperative imaging, intraoperative decision-making, and technical modifications are emphasized as key factors for optimizing patient outcomes. Although this study provides a detailed description of techniques under challenging hysterectomies, its limitation lies in the reliance on schematic illustrations rather than comprehensive intraoperative photographic documentation.